Analysis of Curriculum Administration at the Nurul Islam Karawang Integrated Quran Elementary School - Adzra Emalis Saputra; Astuti Darmiyanti (al-Afkar, Journal For Islamic Studies, 2024)
This research aims to analyze the effectiveness of curriculum administration at Nurul Islam Integrated Quran Elementary School in Karawang. The research methodology involves observational approaches, interviews, and document analysis to evaluate the implementation of a curriculum focused on Quranic teachings. Research findings indicate challenges in resource management and student progress evaluation. The pivotal roles of teachers and stakeholders in curriculum design and implementation are identified as crucial factors. Despite efforts made, obstacles such as limited resources and the expansion of evaluation strategies are still apparent. Research recommendations include enhancing teacher training, increasing parental involvement, and adjusting evaluation approaches to improve curriculum administration effectiveness. This analysis provides in-depth insights into curriculum dynamics in an Islamic educational environment, with the hope of contributing to the development of a sustainable elementary education system aligned with Quranic values.